2015
DOI: 10.1098/rsos.150306
|View full text |Cite
|
Sign up to set email alerts
|

High-content screening identifies a role for Na + channels in insulin production

Abstract: Insulin production is the central feature of functionally mature and differentiated pancreatic β-cells. Reduced insulin transcription and dedifferentiation have been implicated in type 2 diabetes, making drugs that could reverse these processes potentially useful. We have previously established ratiometric live-cell imaging tools to identify factors that increase insulin promoter activity and promote β-cell differentiation. Here, we present a single vector imaging tool with eGFP and mRFP, driven by the Pdx1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…While no alterations in GSIS are observed in Scn9a −/− mice, these mice present higher insulin content relative to wild-type counterparts [12]. Furthermore, Na v 1.7 channel inhibition increases both Ins1 and Ins2 mRNA expression [12]. These data suggest that Na v 1.7 channels may be associated with insulin biosynthesis.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…While no alterations in GSIS are observed in Scn9a −/− mice, these mice present higher insulin content relative to wild-type counterparts [12]. Furthermore, Na v 1.7 channel inhibition increases both Ins1 and Ins2 mRNA expression [12]. These data suggest that Na v 1.7 channels may be associated with insulin biosynthesis.…”
Section: Discussionmentioning
confidence: 85%
“…Alternatively, the Na v 1.7 channel, encoded by Scn9a, corresponds to 85% of the Na + current [30], although its role is yet to be unveiled as the Na v 1.7 channel is inactivated at physiological membrane potentials. While no alterations in GSIS are observed in Scn9a −/− mice, these mice present higher insulin content relative to wild-type counterparts [12]. Furthermore, Na v 1.7 channel inhibition increases both Ins1 and Ins2 mRNA expression [12].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Changes in the activity of Nav1.7 channels may be linked to beta-cell dysfunction and the susceptibility of developing painful neuropathy, because this channel is also expressed in dorsal root ganglion neurons (Hoeijmakers et al, 2014). Recently, it was shown that Nav1.7 channels are linked to insulin production, because pancreatic islets from Scn9a2/2 mice exhibit increased insulin content compared with their wild-type counterparts (Szabat et al, 2015). The latter also offers new perspectives for drugs like carbamazepine, which inhibits the channel and dose dependently increases the mRNA expression of both insulin genes (Ins1 and Ins 2), as well as Pdx1 (a marker of pancreatic beta cells) in isolated islets from mice (Szabat et al, 2015).…”
Section: Historical Overview Of Nav Channels and Insulin Secretionmentioning
confidence: 99%
“…Both of the 2014 landmark papers made use of highthroughput screening, and although this is a powerful technique, some might wonder whether it has taken us off the path of mimicking pancreas development. Despite this concern, high-throughput efforts to identify factors that increase insulin production and promote beta cell differentiation continue in our group and elsewhere [45].…”
mentioning
confidence: 99%